2010
DOI: 10.1371/journal.pcbi.1000768
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Determining Phase Response Curves Reveals that Purkinje Cells Can Act as Perfect Integrators

Abstract: Cerebellar Purkinje cells display complex intrinsic dynamics. They fire spontaneously, exhibit bistability, and via mutual network interactions are involved in the generation of high frequency oscillations and travelling waves of activity. To probe the dynamical properties of Purkinje cells we measured their phase response curves (PRCs). PRCs quantify the change in spike phase caused by a stimulus as a function of its temporal position within the interspike interval, and are widely used to predict neuronal res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
76
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 50 publications
11
76
0
Order By: Relevance
“…A key feature determining the interaction properties is the ability of an oscillator to respond, by shifting its phase, to an external perturbation; this feature is often quantified in terms of phase response curves (PRC), which describe both reactions to a single pulse perturbation and to a continuous force, resulting in a continuous phase shift in the latter case 2,3,7,8 . This approach is used in neuroscience [9][10][11] , cardiorespiratory physiology [12][13][14][15][16][17] and chronobiology 18,19 , to name just a few. A traditional experimental approach to obtain the PRC implies that the oscillator (for example, a neuron) is isolated from the environment (for example, from other neurons that normally interact with it) and is repeatedly perturbed by (weak) short pulses 20 .…”
mentioning
confidence: 99%
“…A key feature determining the interaction properties is the ability of an oscillator to respond, by shifting its phase, to an external perturbation; this feature is often quantified in terms of phase response curves (PRC), which describe both reactions to a single pulse perturbation and to a continuous force, resulting in a continuous phase shift in the latter case 2,3,7,8 . This approach is used in neuroscience [9][10][11] , cardiorespiratory physiology [12][13][14][15][16][17] and chronobiology 18,19 , to name just a few. A traditional experimental approach to obtain the PRC implies that the oscillator (for example, a neuron) is isolated from the environment (for example, from other neurons that normally interact with it) and is repeatedly perturbed by (weak) short pulses 20 .…”
mentioning
confidence: 99%
“…In such cases, the exact BP algorithm, a priori assuming that the recovered signal predicts the measurement results exactly, may fail to converge. Furthermore, the Dantzig selector also applies to cases where the signal is approximately sparse such that many coefficients actually remain nonzero, but their magnitudes decay at least faster than a power law, |⌬ k | ϳ 1⁄k n for a positive integer n. This is important since a PRC can have this property: for example, it has been reported that cerebellar Purkinje neuron can have a square wave-like PRC, indicating neuronal near-perfect integration (Phoka et al 2010), and in this case many Fourier coefficients will be nonzero but decay as |⌬ k | ϳ 1⁄k.…”
Section: Cs Methodsmentioning
confidence: 99%
“…We could not observe similar bias in our simulated or experimental data and did not try to prevent it. However, in principle, we can address this problem in the continuous stimulus paradigm in a similar way as Phoka et al (2010) by using corrections from multiple ISIs: we first make the stimulus-IFRC pair from every two consecutive ISI, such as {T i ϩ T i ϩ 1 } and {[x i , x i ϩ 1 ]}, and estimate the PRC for these two ISIs as [⌬;⌬]. In this way, we can eliminate the effect of the spike time uncertainty in the spike between the i-th and (i ϩ 1)-th ISI.…”
Section: Inclusion Of Uncontrolled Noise and Cs-total Least-squares Ementioning
confidence: 99%
See 2 more Smart Citations